Youth employability in ghetto neighbourhoods: The role of personal agency in reproducing or transforming social structures - Ince, Merlin Ince (Department of Sociology, 2018)
This thesis explores variations in employment outcomes among youth living under similar structural conditions of poverty and unemployment in ghetto neighbourhoods. It challenges structuralist accounts that ignore the role of personal agency and hold that structures alone determine action. The critical realist framework offers a helpful understanding of social structures as both material and cultural since human agency, or action, is influenced by circumstances that are both materially objective and culturally subjective. By probing the interaction of agency and structure this research shows that individual agency is a response to cultural beliefs and competing cultural norms. The ensuing worldview informs decisions and actions of youth which, under different cultures and material family structures, either reproduce or transform their educational and employment prospects in ghetto neighbourhoods. Ten case studies are analysed from youth in Manenberg, Cape Town, a neighbourhood that was historically segregated through the apartheid system of forced removals and resettlement. In-depth interviews provide evidence from life histories, experiences of education institutions and of looking for work. Further information is gathered from interviews with secondary participants, apart from participant observation in family and community activities through an ethnographic approach. Findings reveal that the culture of disengaged parenting leaves youth exposed only to the influence of low education and employment expectations such that they despondently relinquish career aspirations by dropping out of school, remaining unemployed and underemployed as a result. By contrast, consistent mentoring from parents entails a culture that competes with the negative influence of gangs and enables resilience among youth to pursue tertiary education. Youth thereby transform, rather than reproduce, their position in the labour market as unemployed or underemployed unskilled manual workers. Similarly, social networks beyond the neighbourhood provide youth with job information, supportive resources, and cultural capital, which enable them to conceptualise ideas of professional careers. This transforms the historical and contemporary material structure of ghetto neighbourhoods with socially isolated networks that limit youth to low-skilled employment opportunities. Such networks do not support personal agency towards alternative employment and youth resort to cultural practices of gangsterism, irregular and informal work.